Religious Moderation in Puja Mandala: A Study of Inter-religious Dialogue Model in Peace Building - Dwi Ratnasari; Luqyana Azmiya Putri; Abd Razak Zakaria; Nuzulia Febri Hidayati (IBDA` : Jurnal Kajian Islam dan Budaya, 2025)
Puja Mandala, a complex of places of worship in Bali, Indonesia, is a concrete example of religious moderation within a pluralistic society. Featuring five houses of worship representing five significant religions nearby, Puja Mandala is a site for worship and a space for interfaith dialogue that fosters social peace. This research examines how Puja Mandala has developed peace-building principles, such as enhancing inter-religious dialogue, and how it has become a landscape of religious moderation. This study uses a qualitative approach to explore interfaith interactions at Puja Mandala. Through the dialogue of life and action, the Puja Mandala contributes to establishing interfaith harmony. The findings indicate that Puja Mandala is an effective model for implementing religious moderation, mitigating potential conflicts, and strengthening social solidarity through open communication and mutual respect.